Telemonitoring of patients with advanced non-curable diseases: Narrative review and initial experience in the home visit program of the National Center for Pain Control and Palliative Care during the national emergency related to COVID-19 - Carvajal-Valdy, Gabriel (2021)
Telemedicine describes the electronic delivery of medical data for diagnosis, treatment and medical education to the patient at home through the use of information and communication technologies. In just a few weeks, the current global situation related to COVID-19 has generated unprecedented pressures on the health system and transformed the practice of palliative care. The National Center for Pain Control and Palliative Care's home visiting program adopted the teleconsultation modality in March 2020 and a pilot plan for evaluating telemonitoring technology was established. During the initial evaluation period between March and July 2020, a physician specializing in Palliative Medicine reviewed the vital signs within 24 hours of transmission and conducted a teleconsultation of the patient allowing analysis of the data received. A total of 14 patients were monitored for an average of 10.2 ± 3.7 days for a total of 143 days of multiparametric monitoring and 3432 hours of monitoring. The preliminary results of this study suggest a positive effect on symptom control, patient satisfaction, staff education, and communication among team members.